PASTA PRODUCTION FROM FERMENTED CASSAVA FLOUR - Faustina Teguh, Christabelle
Pasta is one of carbohydrates source that is consumed by people in Indonesia. Wheat is used to make pasta because it contains protein in gluten form that has the role to give pasta its specific texture. Wheat is a plant that is difficult to grow in Indonesia which increase Indonesia’s wheat import rates. In Indonesia, there are other crops that could be used as food resource, one of them is cassava. In several occasions, cassava can be produced as flour, which have similar nutrition value as wheat flour. Fermented Cassava Flour (fercaf) is cassava flour which is fermented with lactic acid bacteria. However, fercaf doesn’t contain gluten that is needed to make pasta. This problem is solved by adding additives such as hydrocolloids to give gluten-like feature. In this research, fercaf is used as the main ingredients to make pasta with flour addition such as rice flour, corn flour, and hydrcolloids (Xanthan Game, Guar Gum, Arabic Gum and CMC) to give pasta texture. The research is done by varying the composition, specifically the flour substitute composition and the percentage of hydrocolloids (% w/w). The making process of pasta dough utilize a machine called Renoodle RN 77. Analysises for the pasta includes elasticity, yield, cooking weight, hardness, stickiness and hedonic test to determine the best pasta made from fercaf. Yield and hardness analysis is done before cooking process while elasticity, stickiness, cooking weight and hedonic test is done after cooking process. Through this research, the result shows that fercaf can be used as pasta’s main ingredients. The addition of rice flour and corn flour give strong and elastic texture to the pasta while hydrocolloid addition increase water-binding ability of the pasta. Based on the analysis of the received data, the suitable composition of flour substitute is fercaf:rice flour: maizena varient with 70:10:20 ratio. Hydrocolloid composition chosen is the varient of Xanthan Gum 2,5% with the deliberation of five characteristic aspects and hedonic test.